USING “THE TWO STAY TWO STRAY” TECHNIQUE TO FIND IDEAS FOR WRITING A HORTATORY EXPOSITION TEXT TO THE SENIOR HIGH SCHOOL STUDENTS - Dwi Febriyanti; Saunir Saun (Universitas Negeri Padang, 2013)
This article discusses about a technique in teaching English cooperatively for senior high school students. This technique is called the two stay two stray technique. The teacher divides class into some groups of four students. Each of the groups discusses with their original group about a topic that is given by the teacher and shares the result of their discussion to other groups. The goal of this technique is to help students to find the ideas that will be developed in their writing, especially in writing a hortatory exposition text. Abstrak Artikel ini membahas tentang sebuah teknik pengajaran bahasa inggris secara kooperatif untuk siswa Sekolah Menengah Atas (SMA). Teknik ini dinamakan teknik the two stay two stray. Dalam teknik ini, guru membagi siswa menjadi beberapa kelompok yang terdiri dari empat orang siswa. Masing-masing kelompok mendiskusikan sebuah topik yang diberikan guru bersama kelompok asal mereka dan membagikan hasil diskusi mereka dengan kelompok lainnya. Adapun tujuan dari teknik ini adalah membantu siswa dalam menemukan ide-ide yang mereka dapatkan dari hasil diskusi dan nantinya akan dikembangkan dalam tulisan mereka, khususnya untuk menulis hortatory exposition text.